Responses of Enterococcus faecalis resistance and cytolysin up-regulation to nutrients in constructed mesocosms - Liaqat Ali (Elsevier, 2022)
Spreading of multidrug-resistant bacteria has become a growing and significant threat to environmental and public health. Our understanding of environmental variables such as nutrients which contribute to the dissemination of antibiotic resistance and pathogenesis is still limited. In this study, we operated outdoor mesocosm experiments to evaluate how nitrate and phosphate ions with different concentrations influence on an adaptation of Enterococcus faecalis to aquatic environments. E. faecalis were isolated from the mesocosms at 8 sampling events for 96 days to evaluate biofilm production, quorum-sensing-related genes expression, and sensitivity to oxytetracycline, erythromycin, ciprofloxacin, ampicillin, vancomycin, and chloramphenicol. Quantitative real-time PCR was used to compare mRNA levels of E. faecalis quorum-sensing-related genes. E. faecalis isolates exhibited resistance to oxytetracycline, ampicillin, and ciprofloxacin, respectively. We observed that the biofilm production of E. faecalis isolates on day 60 and 96 was significantly increased (p < 0.01). The expressions of quorum-sensing-related genes were significantly up-regulated (∼tenfold) at the transcriptional level in nutrient-enriched treatments. Our findings indicate that nitrate and phosphate ions facilitate resistance to commonly used antibiotics, increase biofilm production and intra-species communication, which could be a major reviving strategy of E. faecalis in the aquatic environments.